2007
DOI: 10.1111/j.1574-695x.2007.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal disease in Portugal prior to and after the introduction of pneumococcal heptavalent conjugate vaccine

Abstract: The rates of invasive pneumococcal disease (IPD), serotype distribution and antimicrobial susceptibility prior to and after the introduction of the heptavalent pneumococcal conjugate vaccine in Portuguese children were evaluated. The changes in incidence of IPD in children under 1 year old between the two periods of the study was not significant (P=0.53), despite the 21% decline. In children under 18 years old there was a 27.7% decrease in vaccine serotypes. All nonvaccine serotypes increased 71.4%. The decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…In the United States, clonal expansion (the increase in the number of previously rare clones expressing nonvaccine serotypes) has also been documented (2). Nonvaccine serotypes have been reported in a number of postvaccine studies (11,23,27). It is not clear whether such changes are directly driven by vaccine pressure or are due in some part to the natural fluctuations that occur in this naturally transformable species.…”
mentioning
confidence: 99%
“…In the United States, clonal expansion (the increase in the number of previously rare clones expressing nonvaccine serotypes) has also been documented (2). Nonvaccine serotypes have been reported in a number of postvaccine studies (11,23,27). It is not clear whether such changes are directly driven by vaccine pressure or are due in some part to the natural fluctuations that occur in this naturally transformable species.…”
mentioning
confidence: 99%
“…In France, a 21% decrease in IPD among children aged !2 years was observed in 2006 after PCV7 introduction (coverage, 68%; uptake, 44%), whereas the overall rate of IPD among adults increased [27]. In Portugal, with a PCV7 uptake of 54%, the rate of IPD among children aged !1 year decreased by 21% in the period 2002-2004, although the decrease was not statistically significant ( ) [28]. In P p .53 Spain, PCV7 covered 68% of the serotypes that were causing IPD in children during the prevaccine period [13,20], and the estimated PCV7 uptake among children aged !2 years was 22%-29% in 2002-2004 and increased to 45%-50% in 2005-2006 [13-17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that the use of the 7-valent conjugate vaccine is very effective in reducing not only invasive infections but also carriage of vaccine serotypes in the nasopharynx of vaccinated children [17][18]. Although vaccine use causes an Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…increase in herd immunity and a reduction in the number of vaccine-related diseases, the greatest concern is a possible increase in invasive pneumococcal diseases caused by non-vaccine serotypes resulting from the selective pressure of the vaccine [18][19][20]. In this regard, Martens et al [16] have reported that capsular serotypes influenced the outcome of invasive pneumococcal diseases and that infection with serotype 3 resulted in an increased relative risk of death, whereas infection with serotype 1 was associated with a decreased risk of death.…”
Section: Discussionmentioning
confidence: 99%